The GDPR Compliance in Local Government Administration in Poland almost 3 Years after Implementation - Dominika LISIAK-FELICKA; Maciej SZMIT (Communications of International Proceedings, 2021)
The paper contains descriptive exploratory research on the implementation and the data processing process in compliance with General Data Protection Requirements (GDPR) in a group of Polish public administration offices. The research focused on investigating the state of personal data protection in the surveyed entities after almost three years after the GDPR implementation. The questionnaire survey has been performed using the Computer Assisted Web Interview. Opinions about the office compliance with the regulation requirements, personal data breaches, requests from data subjects, external audits and inspections, the GDPR impact on the office, the maturity of processing data and problems in ensuring the GDPR compliant data processing have been gathered. Research findings were compared with previous authors’ studies.
Keywords: General Data Protection Regulation (GDPR); personal data protection; public administration; Information Security Management Systems